Implementation Of The Thematic Learning Process Using A Constructivist Approach - Wiwik Maladerita; jumaris; Solfema (CV. AFDIFAL MAJU BERKAH, 2021)
The aims of this study were to describe the implementation of the thematic learning process using a constructivist approachin the third grade of SDN 05 Alang Rambang Pesisir Selatan. This study uses the classroom action research method and is completed across several stages of planning, implementation, observation, and reflection. The subjectsof the research were the third grade of SDN 05 Alang Rambang Pesisir Selatan. The data collection in the study used two assessments: namely,observation and the assessment sheet. The progress and improvementobtained during the two-cycle learning process shows that through theimplementation of constructivism approaches in the thematic learning process, it canimprove learning outcomes. The research findings show that the use of a constructivist approach can improve the thematic learning process. This increase can be seen from the average percentage of assessment of lesson plans in the first cycle is 73.2, teacher aspect assessment is 57.5, the implementation of student aspects in cycle I is 59.5, while mathematics learning outcomes are 59.7, social studies are 62.73, and Indonesian 65.75. Cycle II the average percentage of assessment of lesson plans in cycle II is 80.25, teacher aspect assessment is 80, student aspect implementation in cycle II is 82, while mathematics learning outcomes are 87.6, Social Studies is 78.5, and Indonesian language is 81.1. The research findings show that the use of a constructivist approach can improve the thematic learning process